Blood parasites in dogs from the Belgrade area in the period 2014-2015 - Pavlović Ivan N.; Kovačević Ivana N.; Doder Radoje B.; Rangelov Branislav R.; Nikić Ivana B.; Tambur Zoran Z. (Zbornik Matice Srpske za Prirodne Nauke, 2017)
Prevalence of blood parasites in dogs in the Belgrade area has been investigated continuously during the last 20 years, especially in clinically suspicious dogs. In the period from 2014 to 2015, 249 blood samples of pets (182) and shelter dogs (67) were examined. Using Giemsa-stained blood smears, the presence of Babesia spp. was examined in erythrocytes and the presence of morulae of Ehrlichia spp. and Anaplasma spp. in circulating monocytes and granulocytes. To confirm positive findings of ehrlichiosis and anaplasmosis in blood smears, CaniV-4 Test Kit or IDEXX SNAP 4DX test was used. Infection with two pathogens was found in 78/249 (31.32%) cases; in all cases, the infection with one of the protozoa or bacteria was in combination with heartworms. In blood-smears, babesiosis was found in 39.75% of pet dogs and in 71.64% of shelter dogs, ehrlichiosis in 15.93% and 28.35%, and anaplasmosis in 6.04% and 19.40%, respectivelly. From colected ticks, relative abundance analysis revealed that the species Ixodes ricinus was absolutely dominant and found in 50.53% (47/93), followed by Rhipicephalus sanguineus ‒ 38.70% (36/93), Dermacentor marginatus ‒ 9.67% (9/93), D. reticulatus, and Ixodes persulcatus found in 3.22% (3/93), which for the first time occurred in dogs in the Belgrade area and in Serbia.